1999
DOI: 10.1007/s001670050117
|View full text |Cite
|
Sign up to set email alerts
|

Articular cartilage regeneration of the knee joint after proximal tibial valgus osteotomy: a prospective study of different intra- and extra-articular operative techniques

Abstract: In this prospective study high tibial osteotomy for medial gonarthrosis was performed in 95 patients (105 knee joints). The patients underwent simultaneously diagnostic and operative arthroscopic surgery of the knee joint. A follow-up arthroscopic examination could be performed in 75 patients (85 knee joints) at the time of implant removal. In group 1 (20 knee joints), the osteotomy was performed after diagnostic arthroscopy without arthroscopic operation of the knee joint. The fixation of the osteotomy was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 27 publications
1
36
0
4
Order By: Relevance
“…However, there were no differences in clinical outcome between groups. Schultz et al reported similar finding in a retrospective comparison of diagnostic arthroscopy, drilling, and abrasion arthroplasty in conjunction with HTO [79]. No difference in clinical outcome was found at 1-year follow-up.…”
Section: Arthroscopy and High Tibial Osteotomysupporting
confidence: 70%
See 2 more Smart Citations
“…However, there were no differences in clinical outcome between groups. Schultz et al reported similar finding in a retrospective comparison of diagnostic arthroscopy, drilling, and abrasion arthroplasty in conjunction with HTO [79]. No difference in clinical outcome was found at 1-year follow-up.…”
Section: Arthroscopy and High Tibial Osteotomysupporting
confidence: 70%
“…Adequate valgus correction was the primary determinant of outcome in both studies. Other authors recommend routine arthroscopy before HTO [79,80]. They stress the low morbidity of the procedure and the ability to treat concomitant intraarticular pathology.…”
Section: Arthroscopy and High Tibial Osteotomymentioning
confidence: 97%
See 1 more Smart Citation
“…Since the differences between mechanical shaving, bipolar chondral coblation and microfracturing are neg- [20]. In older patients, however, methods not requiring with long rehabilitation periods should be used.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Stability of the knee and the absence or correction of malalignment are preconditions for all types of cartilage procedures. [13][14][15] Apart from deformity correction in the coronal plane, osteotomies can strongly influence the sagittal plane by consciously or unconsciously altering the tibial slope. [16][17][18][19] Although being well accepted in the treatment of posterior and posterolateral instabilities, the role of slope modifications in ACL-deficient knees is still not well understood.…”
mentioning
confidence: 99%